2000
DOI: 10.1046/j.1471-4159.2000.0751493.x
|View full text |Cite
|
Sign up to set email alerts
|

Agonist‐Induced Internalization and Recycling of the Human A3Adenosine Receptors

Abstract: Abstract:A 3 adenosine receptors have been proposed to play an important role in the pathophysiology of cerebral ischemia with a regimen-dependent nature of the therapeutic effects probably related to receptor desensitization and down-regulation. Here we studied the agonist-induced internalization of human A 3 adenosine receptors in transfected Chinese hamster ovary cells, and then we evaluated the relationship between internalization and signal desensitization and resensitization. Binding of N 6 -(4-amino-3-[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 40 publications
4
40
0
Order By: Relevance
“…It is of interest that, at the concentration used, ConA only partially inhibited the ability of AVP pretreatment to induce desensitization. This concentration (0·25 mg/ml) has been shown, in some instances, to inhibit completely internalization of a variety of GPCRs (Pippig et al 1995), while in others it only partially inhibited internalization (Trincavelli et al 2000). If receptor internalization was completely inhibited by ConA in the perifused anterior pituitary cell system used in these experiments, the remaining desensitization must have been the result of another desensitization process or processes.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is of interest that, at the concentration used, ConA only partially inhibited the ability of AVP pretreatment to induce desensitization. This concentration (0·25 mg/ml) has been shown, in some instances, to inhibit completely internalization of a variety of GPCRs (Pippig et al 1995), while in others it only partially inhibited internalization (Trincavelli et al 2000). If receptor internalization was completely inhibited by ConA in the perifused anterior pituitary cell system used in these experiments, the remaining desensitization must have been the result of another desensitization process or processes.…”
Section: Discussionmentioning
confidence: 82%
“…The involvement of receptor internalization in the regulation of the ACTH response to AVP was investigated with the lectin concanavalin A (ConA) to block receptor internalization (Pippig et al 1995, Trincavelli et al 2000. The experimental protocol employed was based on that which we have previously used to investigate resensitization of the ACTH response to AVP (Hassan et al 2003).…”
Section: Effect Of Blockade Of Receptor Internalization On the Regulamentioning
confidence: 99%
“…The adenosine A 3 receptor is particularly susceptible to phosphorylation by G protein-coupled receptor kinases [17,50]. Studies using CHO cells stably expressing the A 3 receptors have demonstrated that, following a few minutes of exposure to the agonist, there is rapid phosphorylation of the A 3 receptor, a reduction in number of A 3 high affinity agonist binding sites [16], and receptor internalization [19]. In human astrocytoma cells, brief exposure (1-60 min) to nanomolar concentrations of Cl-IB-MECA results in a rapid uncoupling of A 3 receptors and receptor internalization while a long-lasting (1-24 h) Cl-IB-MECA treatment leads to receptor down-regulation which recovers after several hours [20].…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be attributable to desensitization of A 3 receptors. In fact, both human and rat A 3 receptors are desensitized within a few minutes after agonist exposure [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The OD values were converted to actual pERK concentrations (pg/ml) based on the standard curve of the recombinant pERK standards provided in the kit. For the desensitization studies [20,21], cells were incubated with agonists at 37°C for 24 h. The medium was then replaced with agonist-free medium and cells were treated with an A 3 AR agonist MRS3558 at various time points.…”
Section: Erk1/2 Activation Assaymentioning
confidence: 99%